Antibiotic resistance and virulence factors in lactobacilli: something to carefully consider. (May 2022) - Colautti, Andrea; Arnoldi, Martina; Comi, Giuseppe; Iacumin, Lucilla
Abstract: Lactobacilli are a ubiquitous bacteria, that includes many species commonly found as part of the human microbiota, take part in the natural food fermentation processes, are used as probiotics, and in the food sector as starter cultures or bio-protectors. Their wide use is dictated by a long history of safe employ, which has allowed them to be classified as GRAS (General Recognized As Safe) microorganisms by the US Food and Drug Administration (FDA) and QPS (Qualified Presumption of Safety) by the European Food Safety Authority (EFSA, 2007; EFSA, 2021). Despite their classification as safe microorganisms, several studies show that some members of Lactobacillus genus can cause, especially in individuals with previous pathological conditions, problems such as bacteremia, endocarditis, and peritonitis. In other cases, the presence of virulence genes and antibiotic resistance, and its potential transfer to pathogenic microorganisms constitute a risk to be considered. Consequently, their safety status was sometimes questioned, and it is, therefore, essential to carry out appropriate assessments before their use for any purposes. The following review focuses on the state of the art of studies on genes that confer virulence factors, including antibiotic resistance, reported in the literature within the lactobacilli, defining their genetic basis and related functions. Highlights: Several genes that confer antibiotic resistance are described. Importance of differentiating in intrinsic or acquired antibiotic resistance. Lactobacillus spp. can acquire virulence genes from pathogens. Some lactobacilli have cause adverse effects on humans.